Financial Performance of Public Sector Banks in India : A Post Reform Analysis - Budhedeo, Shradha H.; Pandya, Neha P. (Indian Journal of Finance, 2018)
Bank nationalization was an important landmark in the history of banking in India. In order to serve the development needs of the country, nearly 20 commercial banks were nationalized between 1969 and 1980. This brought nearly 80% of the banking industry under the government control. For two decades, public sector banks dominated the banking space and exhibited enhanced performance. However, in the late 1980s, the performance and growth of public sector banks started waning, confronted by problems of low productivity and high costs. This called for an urgent need for reforms in the banking industry. After the introduction of financial sector reforms in 1993, the public sector banks could not sustain competition from new-generation tech-savvy private banks. Despite attempts of the government to revive the banking industry, public sector banks continued to show poor performance and accumulating NPAs. After the global financial crisis in 2007, India witnessed economic slowdown and subsequent recession. During this phase, private banks started eclipsing the banking scenario, surpassing the performance of public sector banks. With major share of public sector banks in the country’s banking business, it becomes imperative to examine the financial performance of the public sector banks in India. Time series data were engaged for the study. Financial performance of the public sector bank group was examined and evaluated on the basis of selected financial parameters. The entire time period of the study from 1995-96 to 2016-17 was fragmented into two phases, Phase I being the period immediately following reforms and before the financial crisis set in (1995 - 96 to 2006 - 07), and Phase II coinciding with the post global financial crisis period (2007 - 08 to 2016 - 17). The study concluded that all indicators of financial performance of the public sector bank group showed positive trends during the first phase ; whereas, they exhibited falling trends over the second phase of the analysis period.